The Militaristic Pandemic Response of Duterte: How Did It Affect Social Movements? - Fenis, Magello Rainer (IKAT: The Indonesian Journal of Southeast Asian Studies, 2023)
This article is based on extensive original research that aims to examine how the opposition movement against Duterte employed various mechanisms of political engagement, shaped by the administration’s lockdown-centric response amid the COVID-19 pandemic. Although the pandemic impacted individual social mobility, motivations and forms of political participation were still observed both physically and in the digital world. The study employs a qualitative approach, drawing on data from secondary sources to analyze the interplay between the administration’s governance strategies and the actions of political interest groups during the COVID-19 pandemic. By using rational choice theory, we gain a clearer understanding of Duterte's perceived interests and goals, as well as the costs and benefits of resistance during the pandemic lockdown. The findings show that the Duterte administration's policies curtailed physical forms of political engagement, often described as “militarized” and “police-centric,” thus shaping opposition dynamics and forms of dissent. Despite this, the civil society fostered alternative spaces for resistance, such as community pantries and digital activism. While existing literature has largely focused on democratic backsliding in the context of combating COVID-19, the novelty of this study is its nuanced exploration of the practicality of militaristic measures. Although the Duterte administration’s militarized response did not achieve the expected outcomes in terms of managing the health crisis and suppressing opposition, it still represented the most practical strategy for controlling pandemic dissent. These insights contribute to understanding how government responses to the COVID-19 crisis influence the behavior of both the state and civil society.